Assessment the Quantity and Quality of Un confined Aquifer Resources Located Between Al-Sanawbar and Al-Kabir Al-Shimali Rivers - صبوح حسام; جعفر رائد; عوض عادل; متوج هاديا (Latakia University Journal -Engineering Sciences Series, 2020)
Water is one of the most valuable natural resources, and as a result of increased depletion of those resources with the development of human society, it has become necessary to monitor the quantity and quality of this water, and manage it in a good way. The research aims to study the groundwater system in the area located between Al-Sanawbar and Al-Kabir Al-Shimali rivers, and to evaluate the groundwater resources in terms of quantity and quality, through conducting periodic measurements of the depths of the groundwater, and concentrations of nitrate and phosphate ions, in a monitoring network consisting of 30 wells distributed throughout the research area. The results of the study showed a fluctuating in the depths of groundwater ranging between 0.35 and 17.6 m, and that groundwater generally drains towards river valleys and the sea. The results indicated that the values of the monthly average of nitrate ion exceeded the permissible standards for drinking water in 43% of the studied wells, and 17% of wells exceeded the required standards for irrigation water according to the Syrian standard specification. As for the phosphate anion, it exceeded the permissible standards for drinking water in 40% of the wells, while all wells achieved the required standards for irrigation water.